Analisis Dampak Judi Online di Indonesia - Annisa Laras; Najwa Salvabillah; Cindy Caroline; Jusini Delas H; Farra Dinda; Mic Finanto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Online gambling has become an increasingly worrying issue in Indonesia because of its very dangerous influence on society. This research aims to analyze the social, economic and psychological impacts of online gambling in Indonesia through qualitative methods with a case study approach. Data was obtained from various sources, including previous research, reports from related institutions, as well as information found online. The research results show that online gambling addiction has a very significant negative impact and various factors that cause the increase in online gambling addiction include easy access, aggressive promotion of various types of online gambling on the market. Articles related to online gambling are regulated in Law article ITE 27 section 2, but law enforcement still faces many obstacles. Handling by the police and government needs to be improved through collaboration with related institutions and strict law enforcement. The implications of these findings indicate the need for stricter policy interventions as well as education and rehabilitation programs to reduce the negative impact of online gambling on Indonesian society. Effective methods to help individuals quit online gambling addiction include psychological counseling, social support, and developing stress and emotion management skills.